The role of the surgeon in cancer care. Issue 3 (March 2018) - Elder, Kenneth; Barber, Matthew D.
Abstract: The surgeon's role in modern cancer management has evolved beyond that of technician with a scalpel and now encompasses a wide ranging role in diagnosis, counselling, screening, prevention, resource management and palliative care as well as the traditional role of surgical excision. Many surgeons also have an active academic interest at teaching hospitals, conducting cancer research and teaching in associated medical schools. The UK has three established cancer screening programmes for breast, cervical and colorectal cancer, where surgeons are required to perform clinical assessment, diagnostic biopsies and plan surgical treatments. In addition to this there is also a screening programme in place for the early detection and treatment of abdominal aortic aneurysms. The multidisciplinary team (MDT) remains the cornerstone of cancer treatment in the UK and each oncological subspeciality has regular meetings to discuss tailored cancer treatment for each individual. Alongside oncologists, radiologists, specialist nurses and pathologists, the surgeon is a key member of this team and in the decision making process. There are many different surgical techniques available for surgical treatment of cancer, many of which allow a minimally invasive approach including laparoscopic, endoscopic and robotic surgery. The progress of medical genetics and gene profiling now allows identification of 'at-risk' individuals for specific types of cancer where prophylactic or risk reducing surgery may be of benefit. Cancer treatment may result in disfigurement and loss of function, so reconstructive surgery is now an integral part of cancer management. Patients with advanced disease can often be helped by surgery to relieve symptoms and improve the quality of their remaining life and so the surgeon may play a key role in end-of-life care.